Providing Basic Life Support Training on Improving Knowledge and Skills of Police Personnel in The Brimob Work - Rahman, Abdul; Rahman, Mahmud; Fhirawati, Fhirawati; Sainah, Sainah (Advances in Healthcare Research, 2024)
Purpose: This research aims to determine the effect of providing basic life support training on increasing knowledge and skills among police personnel in the East Kalimantan Regional Police Mobile Brigade Unit. Research Design and Methodology: The research method employed is a quantitative experimental design with a quasi-experimental approach, which allows for some flexibility in randomization while also controlling validity threats. The design used in this study is a non-equivalent control group design, which involves a comparison group (control) (Notoatmodjo, 2010). Findings and Discussion: Basic Life Support (BLS) training improves police knowledge and skills. This quasi-experimental study, conducted among 546 Brimob officers, demonstrated significant gains in the intervention group following training. Knowledge and skill scores rose significantly, demonstrating the effectiveness of training. Brimob members are encouraged to apply BLS and share their experience with fellow officers. Implications: It is hoped that the East Kalimantan Regional Police Mobile Brigade work unit environment can provide BLS education in stages to all member personnel and conduct personal tests to assess the skills they have acquired.